2019
DOI: 10.32491/jii.v18i3.382
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity conservation of coastal fish of Indonesia

Abstract: Each species has a special value. No species was created without intention. If one species matters, all species are altogether admirably important. This paper elucidates critical importance of species conservation in the context marine fish biodiversity in Indonesia. This resource endowment has not been truly known and hence improperly utilized. As direct consequences, biodiversity loss and species extinction are unstoppable trend. This condition is attributed to the lack systematic research and serious educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…According to the results of the research, the number of coral fish species found was 233 species (37 308 individuals) with a composition of 27 species (557 individuals) indicator fish, 96 species (13,578 individuals) target fish, and 115 species (23,173 individuals) major fish. The results of a coral fish study conducted by Allen and Erdman [31] in Nikijuluw [32]…”
Section: Coral Fishmentioning
confidence: 99%
“…According to the results of the research, the number of coral fish species found was 233 species (37 308 individuals) with a composition of 27 species (557 individuals) indicator fish, 96 species (13,578 individuals) target fish, and 115 species (23,173 individuals) major fish. The results of a coral fish study conducted by Allen and Erdman [31] in Nikijuluw [32]…”
Section: Coral Fishmentioning
confidence: 99%
“…Invertebrata laut juga memiliki potensi fungsi imunologi ekologis (Ellis et al, 2011). Meskipun demikian, invertebrata laut juga memiliki potensi ancaman dari spesies invasif non-native (Hughes et al, 2020), manusia dan proses alami (Wilkinson, 2004), Sementara itu banyaknya spesies invertebrata laut yang belum teridentifikasi (Mangubhai et al, 2012;Nikijuluw, 2017) dan memiliki sifat dimorfisme, perubahan morfologi selama perkembangan dan penyimpanan spesimen (Ward et al, 2009) menyebabkan kendala pendekatan morfologi untuk identifikasi invertebrata laut. Apalagi bila spesimen invertebrata rusak (Schander & Willasen, 2005), masalah umur sampel (Webb et al, 2006) dan beberapa spesies tampak samar secara morfologi sehingga identifikasi makin sulit (Muchlisin et al, 2013).…”
Section: Pendahuluanunclassified
“…The sustainability of aquatic species will be significantly impacted by human activity in coastal waters, either directly or indirectly. Human activities such as habitat modification, overfishing, the introduction of alien species, and natural causes like sea level rise and global climate change may pose some threats to the ichthyofauna diversity of a water region (Nikijuluw 2018).…”
Section: Introductionmentioning
confidence: 99%